1991
DOI: 10.1108/eum0000000001268
|View full text |Cite
|
Sign up to set email alerts
|

The Different Operations Strategy Planning Process for Service Operations

Abstract: The manager who moves from manufacturing to services or the professor who wishes to research and teach service operations must recognise the key differences for developing an appropriate operations management strategy in a service business. For this process to be successful, the operations manager must participate assertively in the strategy debate. In manufacturing it is important that the functional strategy supports the corporate strategy in the marketplace and is co‐ordinated with other functional strategi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
1

Year Published

1991
1991
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 14 publications
0
22
1
Order By: Relevance
“…Davidson and Haspeslagh's (1982) study also found the matrix structure doing a better job in new product introduction and sales growth than the multidivisional structure for international operations. Theoretical arguments in favor of 'matrix structures at high levels of product and market diversity have been forwarded by Davis and Lawrence (1977), Miles and Snow (1978), and Galbraith and Kazanjian (1986).…”
Section: H3: When Foreign Productlservice Diversity Is Relatively Lowmentioning
confidence: 99%
See 1 more Smart Citation
“…Davidson and Haspeslagh's (1982) study also found the matrix structure doing a better job in new product introduction and sales growth than the multidivisional structure for international operations. Theoretical arguments in favor of 'matrix structures at high levels of product and market diversity have been forwarded by Davis and Lawrence (1977), Miles and Snow (1978), and Galbraith and Kazanjian (1986).…”
Section: H3: When Foreign Productlservice Diversity Is Relatively Lowmentioning
confidence: 99%
“…Therefore, it is probably at this business and operational level of service MNCs that the need for strategy-structure fit is more crucial. For backroom operations and subsidiary head office relationships, the information need may be similar to manufacturing MNCs because this part of the system is sufficiently buffered from the customer (McLaughlin, Pannesi and Kathuria, 1990). As a result, the strategy-structure fit at the corporate level may not be significantly different than the manufacturing ones.…”
Section: 10mentioning
confidence: 99%
“…Most of the operations oriented articles focus narrowly on issues of hospital and health care operations such as cost containment, capacity planning or personnel scheduling. We argue, however, that operations encompass a much broader range of decisions than those currently found in the literature, and are a significant factor in health care strategic planning and management.Research on operations strategy in the service sector is relatively new (McLaughlin et al, 1991;Roth and van der Velde, 1991), and it has yet to greatly influence hospital strategic planning. In one notable exception, Roth (1993) discussed her re-0272-6963/96/$15.00…”
mentioning
confidence: 99%
“…Research on operations strategy in the service sector is relatively new (McLaughlin et al, 1991;Roth and van der Velde, 1991), and it has yet to greatly influence hospital strategic planning. In one notable exception, Roth (1993) discussed her re-0272-6963/96/$15.00…”
mentioning
confidence: 99%
“…High-contact processes deal with customer-induced variability, while low-contact processes, the technical core, are focused on possible economies of scale and maximising process efficiency. The view that processes devoid of customer contact can be made as efficient as assembly lines in manufacturing operations is widely supported by the existing OM literature (Levitt, 1972;McLaughlin et al, 1991;Silvestro et al, 1992;Collier and Meyer, 1998;Verma and Young, 2000).…”
Section: Reduce Customer Contactmentioning
confidence: 83%